(untitled) (Revista de História Regional, 2007)
The aim of this paper is to discuss the articulation of the Imperial Ar-chaeology related to knowledge and power. From this articulation some matters are raised about the relationship between the archaeological practice and the Imperial political scheme in the context of their stabilization.